Three year follow up of a reattached incisor - (:unkn) unknown (My University, 2000)
Bu yazıda kronu tamamen kınk olan bir üst çe¬ne santral kesici diş vakası anlatılmıştır. Sant¬ral kesici diş basketbol oyunu sırasında kaza ile kırılmış. Endodontik tedavi ve post uygulanım-larını takiben kırık parça ve kalan diş yüzeyi periodontal flap operasyonunu takiben adeziv materyallerle restore edilmiştir. Yerine tekrar uygulanan diş, rezin iyonomerle (Geristore) intrakronal olarak ve mikrohibrid kompozit ile (Clearfil APX) bukkoservikal olarak restore edilmiştir. Klinik muayenede üç yıllık kontroller sağlıklı bir diş eti ve iyi bir kenar uyumu göste¬rirken, röntgen bulguları kanal içi yaygın bir radyolusent alan ortaya çıkartmıştır.

A case report of the maxillary central incisor with a complete crown fracture was presented in this paper. The central incisor was broken accidently in a basketball game. Following en¬dodontic therapy and the post restoration, the fragment and the remnant tooth surface were prepared for adhesive restoration by prepara¬tion of a periodontal flap. The reattached to¬oth was restored with the application of the resin ionomer (Geristore) intracoronally and, a microhybrid composite resin (Clearfil APX) at the buccocervical direction. Although three year recall showed healthy gingiva and good marginal adaptation in clinic examination, the x-ray illustrated an extensive radiolucency in the canal.
Reataçment tedavili bir kesicinin üç yıllık prognozu
Keywords: Diş Hekimliği